Recent museum expansions housed in historic buildings in São Paulo city, Brazil: um estudo comparativo - Rosário da Silva, Marcus Vinicius; Walbe Ornstein, Sheila (Revista de Arquitectura, 2024)
Museums are expanding their role beyond collections and have made efforts to improve the experience of visitors. In this sense, the article aims to understand the expansion of relevant museums installed in historic buildings and provide a critical analysis of the recent expansion with exhibition spaces in the city from São Paulo. To this end, a comparative analysis is adopted whose scope includes verifying similarities that develop in a specific socio cultural scenario and reading the scenario based on different criteria at 1) macro, 2) meso and 3) micro scales. The results are expected to demonstrate whether (or not) criteria related to the integral context, accessibility and inclusion, flexibility and adaptability, environmental and heritage dimensions are met. The practical implications of this study are related to the conditions for the development of general expansion planning in museums and the identification of emerging needs present in historic buildings that house museums.